Membangun Karakter Qur’ani: Telaah Pemikiran KH. Hasyim Asy’ari dan Peran Filantropi Abata Movement dalam Pendidikan Islam - Iftitiyani, Warohma; Baidi, Baidi (Lembaga Yasin AlSys, 2025)
This study examines the relevance and implementation of KH. Hasyim Asy’ari’s thought on Qur’anic character education within the context of contemporary Islamic philanthropic institutions, focusing on the Abata Movement Indonesia Foundation. Employing a descriptive qualitative approach through literature review and case study, the research explores the values of adab in Adab al-‘Ālim wa al-Muta‘allim and their actualization in Abata’s educational programs. The findings reveal that character principles such as sincerity (ikhlāṣ), reverence (ta‘zīm), discipline, and exemplary conduct, as taught by KH. Hasyim Asy’ari, have been consistently internalized through habituation activities, teacher role models, and spiritual development for the children under Abata’s care. The actualization of these values serves as a bridge between classical Islamic thought and the demands of modern character education, particularly relevant amid today’s moral and social crises. The study concludes that integrating the intellectual legacy of classical scholars with institutional innovation in Islamic philanthropy plays a strategic role in shaping a Qur’anic generation—one that is not only knowledgeable and virtuous but also capable of contributing meaningfully to society. The implication is that such an approach may serve as a model for community-based Islamic character education.